Fa’aliyah Ta’allum al-Lughah al-Arabiyah Bistikhdam Wasilah Impress Libre Office Li Tarqiyah Isti’ab al-Mufradat Laday Thullab as-Shaf as-Shabi’ fi al-Madrasah ats Tsanawiyah bi Ma’had Dar al-Hikmah Pekanbaru - Triana Susanti (STAIN Bengkalis, 2020)
The instructional media is necessary. The media helps the teacher in displaying the studied materials, especially teaching vocabulary. In Madrasah Tsanawiyah Pesantren Darul Hikmah, the teacher teaches vocabulary using teaching aids (Arabic language book, dictionary and blackboard). Unfortunately, the students did not understand the vocabulary. This research is an experimental research which is aimed at discovering whether the implementation of Impress Libreoffice Media in learning Arabic is effective to Increase Students’ Mufradat Mastery at Madrasah Tsanawiyah Pesantren Darul Hikmah Pekanbaru. The formulation of the problem in this research is whether the implementation of Impress Libreoffice Media in learning Arabic is effective to Increase Mufradat Mastery of class VII Students’ at Madrasah Tsanawiyah Pesantren Darul Hikmah Pekanbaru.The techniques of data collection are (1) observation and (2) test. While to analyzed the observation the observed data, the researcher used the formula:p= (f/N) x 100% and to analyze the test data, the researcher used SPSS program. The data analysis result gained from the application of Impress Libreoffice in Learning Arabic is effective to develop Mufradat Mastery of the students of class VII Students’ at Madrasah Tsanawiyah Pesantren Darul Hikmah Pekanbaru, based on counting result using statistic To score and SPSS by Mann-Whitney test.